Next-generation sequencing improves precision medicine in hearing loss - Imizcoz, T.; Prieto-Matos, C.; Manrique-Huarte, R.; Calavia, D.; Huarte, A.; Pruneda, P. C.; Ordoñez, G. R.; Cañada-Higueras, E.; Patiño-García, A.; Alkorta-Aranburu, G.; Manrique Rodríguez, M. (Frontiers in Genetics, 2023)
Background. An early etiological diagnosis of hearing loss positively impacts children's quality of life including language and cognitive development. Even though hearing loss associates with extremely high genetic and allelic heterogeneity, several studies have proven that Next Generation Sequencing (NGS)-based gene panel testing significantly reduces the time between onset and diagnosis.In order to assess the clinical utility of our custom NGS GHELP panel, the prevalence of pathogenic single nucleotide variants, indels or copy number variants was assessed by sequencing 171 nuclear and 8 mitochondrial genes in 155 Spanish individuals with hearing loss.A genetic diagnosis of hearing loss was achieved in 34% (52/155) of the individuals (5 out of 52 were syndromic). Among the diagnosed cases, 87% (45/52) and 12% (6/52) associated with autosomal recessive and dominant inheritance patterns respectively; remarkably, 2% (1/52) associated with mitochondrial inheritance pattern. Although the most frequently mutated genes in this cohort were consistent with those described in the literature (GJB2, OTOF or MYO7A), causative variants in less frequent genes such as TMC1, FGF3 or mitCOX1 were also identified. Moreover, 5% of the diagnosed cases (3/52) were associated with pathogenic copy number variants.Conclusions. The clinical utility of NGS panels that allows identification of different types of pathogenic variants -not only single nucleotide variants/indels in both nuclear and mitochondrial genes but also copy number variants -has been demonstrated to reduce the clinical diagnostic odyssey in hearing loss. Thus, clinical implementation of genomic strategies within the regular clinical practice, and more significantly within the newborn screening protocols, is warranted.